Local analgesia by percutaneous electrical stimulation of sensory nerves - Hiedl, P.; Struppler, A.; Gessler, M. (Pain (Amsterdam), 1979)
Experimental C-fiber pain caused by radiant heat was applied to the skin area supplied by the left sural nerve of 20 subjects. Percutaneous electrical stimulation (PNS) was performed on the left sural nerve, the left superficial peroneal nerve and the right superficial radial nerve. Stimulation frequencies were: 3, 50, 100, 300, 500 and 1000 Hz. The analgesia resulting at the different stimulation sites was recorded according to a preset scale of estimation. Without considering the influence of the different frequencies, the best analgesic effects were reached if noxious heating and PNS were both performed on the left sural nerve; the anatomical conditions prevented us from distinguishing between the effects of possible peripheral blockade or spinal modification of pain. PNS of the superficial peroneal nerve seems to indicate spinal, possibly polysegmental, interactions between C-fiber pain and electrical stimulation of thick myelinated fibers. However, long loop effects may also play a part in local analgesia as demonstrated by PNS of the right radial nerve.